Intestinal protozoan parasites with zoonotic potential in birds - Marietto-Goncalves, G. A. [UNESP]; Fernandes, T. M.; Silva, R. J. [UNESP]; Lopes, Raimundo Souza [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Springer, 2008)
The aim of this study was to evaluate the occurrence of potentially zoonotic intestinal protozoan infections in exotic and wildlife Brazilian birds. Fecal samples from 207 birds of 45 species were examined. Infections by Balantidium sp., Entamoeba sp., and Blastocystis sp. were observed in 17 individuals (8.2%) of Gnorimopsar chopi, Oryzoborus angolensis, Sporophila caerulescens, Ramphastos toco, Aratinga leucophtalmus, and Pavo cristatus.